Reglamento de admisión y empleo, manual de funciones y valuación de puestos para la empresa distribuidora Indaura Gutiérrez de la ciudad de Loja - Pozo Esparza, Danny Patricio (2015)
This research entitled "REGULATION OF ADMISSION AND EMPLOYMENT MANUAL FEATURES AND VALUATION OF POSITIONS FOR POINTS FOR DISTRIBUTION COMPANY INDAURA GUTIERREZ OF THE CITY LOJA" describes some of the tools used for better talent management within the company, as an example a convenient way to give each employee the wages commensurate with their duties performed. In the first instance is the Framework, which refers to basic concepts regarding Function Manual, Rules of Admission and Employment and Methods of Valuation of Posts. Then describes the materials, methods and techniques for collecting information that allowed the execution of this work. The results obtained through the interview with the manager of the company, and the 17 surveys applied to different employees thereof, results after being tabulated gave us a closer diagnosis of the reality of human resource exposed the company. Following this we find the proposal of a Manual Functions the same as in its content describes the nature of the position, roles and responsibilities, minimum requirements, working conditions and skills required for each job, plus Admission regulations and Employment, in which the phases of a proper recruitment, selection, recruitment, induction and training for staff of the company is described. As for Posts and functions given to each of the employees of the company, one Recording from Points, for which purpose valuation factors such as Skills and Knowledge, Responsibility, Effort and conditions was first established was conducted work, then the grades for each factor was determined weighting factors was performed giving Knowledge 35%, Responsibility 20% Effort 20% Working conditions 25%, then the points are fixed for the grades and were scored each of the existing posts in the company, making a summation of each position was obtained that the Managing reached 185 points, Secretary 105 points Counter 175 points, Assistant Accounting 125 points, Sales Supervisor 160 points, Sales Executives 200 points, 145 points Mercaderista, Bodeguero 220 points, 240 points and Driver Dispatcher 215 points, tabulated and using mathematical formulas obtained the graph of wage adjustment in accordance with the functions, knowledge, experience, initiative, personal responsibility, responsibility for equipment, effort and risks in your workplace, resulting in need pay adjustment positions Sales Executive, Bodeguero, Driver and dispatcher. Finally, conclusions and recommendations as annexes and bibliography of this investigation is exposed